Aplicación de técnicas de maduración húmeda en carne bovina para el mejoramiento de las características mecánicas, fisicoquímicas y microbiológicas - Intriago Vera, Samira Lizbeth (2024)
This research focuses on the factors that affect the maturation of meat, which is a key process to improve its quality. Variables such as time, temperature, relative humidity and exposure air speed were analyzed, which influence the shelf life and composition of the meat, this experimental study lasted 28 days, with the respective analyzes being carried out on days 7, 14, 21 and 28, maintaining a constant temperature of 2 °C and a relative humidity of 90%. A completely randomized design (DCA) was applied with four treatments and three replications for each one, giving a total of 12 experimental units. Each experiment consisted of approximately 1.2 kg of beef loin center, the variables evaluated were texture profile analysis, to quantify hardness, cohesion, adhesiveness, adhesive force, gumminess, elasticity and chewiness, requiring 12 pieces for the entire experiment. Which are equivalent to 14.4 kg of loin center, the loin pieces were acquired from the tercenas of the Canton Bolívar. T1 with a maturation of 7 days was obtained as the best treatment in terms of adhesiveness and adhesive strength, where this treatment showed the lowest value for adhesiveness, which indicates that the meat was less sticky compared to the other treatments. It is important to keep in mind that these results were obtained under specific conditions of temperature and relative humidity, and may vary depending on other factors such as the breed of cattle, the level of intramuscular fat and other aspects of the maturation process. Therefore, further studies are needed to confirm these findings and determine the best treatment in terms of texture characteristics under different conditions.